The Moral Tale in France and Germany 1750-1789 - Astbury, K (Voltaire Foundation, 2017)
Between 1761 and 1780 the Contes moraux of the self-proclaimed inventor of the moral tale, Jean-François Marmontel, were republished more times than Rousseau’s La Nouvelle Héloïse. They were an instant success throughout Europe and imitators quickly capitalised on readers’ enthusiasm for the moral tale. In fact Marmontel was merely exploiting a growing tendency towards using short fiction in the periodicals of the time and his achievements can only be understood in a wider context. The moral tale came into being in the 1750s in response to a new cultural climate in both France and Germany which focussed on morality and virtue as a means to regenerate society. Authors soon came to see the potential for social comment in their depiction of contemporary society and the moral tale became a form of popular expression of enlightened ideas about injustice, the position of women in society, poverty, the relationship between the growing middle classes and the aristocracy, between citizens and the state. This move towards greater political comment took place against the backdrop of literary developments, as writers exploited the vogue for sensibility and became more aware not only of the specific nature of short fiction, but also of the demands of a growing reading public who had changing tastes and expectations. Realism in terms of plot, structure, characterisation and narration in the moral tale all undergo transformation as the century progresses, primarily because many of the leading literary figures of the period wrote moral tales, from Diderot to Wieland, Louis-Sébastien Mercier to Sophie von La Roche. But the moral tale does not just reflect the development of literary, social and political issues, it also evolves in its own right. By the 1780s the German moral tale had become distinct from the French model, and increasingly its focus on frameworks and other narrative devices prepared the way for the Novelle. Acknowledgements Abbreviations Introduction 1. Marmontel in context 2. The beginnings of the German moral tale 3. The major trends of the 1760s in France: the impact of Marmontel, Rousseau and sensibilité 4. The impact of Rousseau, Goethe and Empfindsamkeit on the German moral tale of the 1770s and early 1780s 5. Social and political criticism in the French moral tale 6. Social and political criticism in the German moral tale 7. Literary developments in the French moral tale 8. Literary developments in the German moral tale Conclusion Bibliography Index of individual tales Index